2017
DOI: 10.20944/preprints201711.0190.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hybrid GA-PSO Optimization of Artificial Neural Network for Forecasting Electricity Demand

Abstract: In the present study, a hybrid optimizing algorithm has been proposed using Genetic Algorithm (GA)and Particle Swarm Optimization (PSO) for Artificial Neural Network (ANN) to improve the estimation of electricity demand of the state of Tamil Nadu in India. The GA-PSO model optimizes the coefficients of factors of gross state domestic product (GSDP) , per capita demand, income and consumer price index (CPI) that affect the electricity demand. Based on historical data of 25 years from 1991 till 2015 , the sim… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Similarly, from Figure 8 , it can be seen that among the records of documents that reach HAP, the average MAPE value is lower in the frameworks that implement hybrid models of ML and multivariate dependency, such as those developed in [ 6 , 27 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. To verify the hypotheses of the differences in the means and variances in the MAPE, three hypothesis tests are carried out.…”
Section: Evaluation Of Model Accuracymentioning
confidence: 85%
See 1 more Smart Citation
“…Similarly, from Figure 8 , it can be seen that among the records of documents that reach HAP, the average MAPE value is lower in the frameworks that implement hybrid models of ML and multivariate dependency, such as those developed in [ 6 , 27 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. To verify the hypotheses of the differences in the means and variances in the MAPE, three hypothesis tests are carried out.…”
Section: Evaluation Of Model Accuracymentioning
confidence: 85%
“…The ANN models have been used in many studies for electric power forecasting [ 6 , 39 , 44 , 46 , 48 , 53 , 54 , 55 , 57 , 58 , 59 , 60 , 61 , 62 , 65 , 70 , 75 , 77 , 81 , 82 , 86 , 108 , 153 , 155 , 165 , 175 , 176 ] and have reached a forcasting accuracy with an average MAPE value of 3.781%.…”
Section: Classes Of Forecasting Modelsmentioning
confidence: 99%
“…Aouni et al (2017) noted a need to aggregate several choices simultaneously to take decisions where accounting objectives are conflicting. Anand and Suganthi (2018) used ANN with different optimisation methods which are also useful to forecast electricity demands. Habib et al (2018) showed that well-documented high-quality financial reports contribute to economic growth.…”
Section: Neural Networkmentioning
confidence: 99%